Global palaeogeographical implication of acritarchs in the Upper Ordovician - Yan Kui; Thomas Servais; Huang Bin; Li Jun; Shan Longlong (Estonian Journal of Earth Sciences, 2023)
The EarlyâMiddle Ordovician peri-Gondwana and Baltica acritarch provinces are easily recognizable, illustrating a clear provincialism of global phytoplankton. However, acritarch assemblages have been reported to become increasingly similar towards the Late Ordovician, revealing a general cosmopolitanism, although, based on more recent studies, their assemblages from Laurentia and Baltica are reported to be rather different from those from peri-Gondwana. In this decade, new acritarch assemblages reported from South America, the Baltic region, Iran and Siberia, as well as the new material from South China and Tarim, provide additional data that help to understand the palaeobiogeographical distribution and evolution of phytoplankton during the Late Ordovician in more detail.